Fenomen „Państwa Islamskiego” i jego źródła - Wojciechowski, Sebastian (Przegląd Strategiczny, 2016)
The aim of the text is to present and systematize the most important reasons for the „Islamic State” dramatic rise to power and significance. The reasons are the sum total of a number of diverse and mutually linked factors. These fall into the three categories: A. effective use of hard power connected to military activities and terrorist attacks; B. appropriate use of soft power concerning financial, logistics or propaganda sphere; C. different events of processes of local or international character. These three groups of factors and their interactions result in the so-called triad of the „Islamic State” phenomenon.